The effect of adding lycopene on improving the characteristics of diluted and cooled semen of Arabi rams - Mashael Mohammed Abdulwahid, Mashael Mohammed Abdulwahid; Al-Asadi, Falah (University of Thi-Qar Journal of agricultural research, 2025)
The experiment was conducted in the animal field of the College of Agriculture / University of Basrah / Karma Ali site for a period of three months from 10/15/2023 and in the forest 1/15/2024. Four Arabian rams were purchased from local markets in Basra Governorate, at ages ranging from 2.5 to 3 years and with similar weights. They were fed a diet consisting of a fodder mixture consisting of barley, bran, hay, and some mineral salts, clean water was provided to them inside the barn. The rams were trained in the process of collecting semen using the artificial vagina of rams in the animal field for a period of two weeks. After completing their training, semen was collected from them three times a month, and after the end of the training period, semen was collected three times a month. The study included adding different levels of lycopene (0,0.5,1,1.5 ) g/100 ml, and the tubes were closed tightly and placed in the refrigerator, and after the temperature stabilized at (5°C) for (0,24,48,72) hours, All characteristics of diluted and cooled semen were measured using a computer (CASA).